El canvi lingüístic i els conflictes de la naturalitat: les desinències del present de subjuntiu - Pérez Saldanya, Manuel (Caplletra. Revista Internacional de Filologia, 1996)
I trace here the evolution of present subjunctive markers in Catalan and, in general, in those Romance languages where the fall of final unstressed vowels allows exemplification of the tendencies toward morphological optimization, as well as some of the naturalness conflicts produced among the different tendencies. The morphological tendencies which appear most active when it comes to a developmental explanation are, in this order, iconicity, transparency, and universality. I also analyze the etymology of the different markers and the three different types of innovations; specifically: (i) the morphologization of vocalic segments which originally had merely a phonological value; (ii) analogical generalization in the first conjugation of the affix characteristic of. the second and third conjugations; and (iii) the reanalysis of segments belonging to the end of the root or to the root extension of some verbs of conjugations other than the first.